Antimicrobial activity of banana (Musa paradisiaca L.) peels against food borne pathogenic microbes - Mohd Sirajudin, Zuvairea Nazren; Ahmed, Qamar Uddin; Khan Chowdhury, Ahmed Jalal; Kamarudin, Zawane; Khan, Abdul Viqar; Uddin, ABM Helal; Musa, Najiah (Journal of Pure and Applied Microbiology, 2014)
Banana (Musa paradisiaca L.) peels are usually considered as wastes and are discarded during the processing, which eventually contribute to polluting the environment. Hence, this study was aimed to evaluate the antimicrobial activity of two different varieties of M. paradisiaca peels, i.e., Nangka (M. paradisiaca variety Nangka)and Tanduk (M. paradisiaca variety Tanduk) with regard to generate safe and cheap antimicrobials as well as address pollution related issues due to such wastes. Antimicrobial study was carried out on the extracts using disc diffusion and broth micro-dilution methods. The best activity through disc diffusion method for bacteria and fungi was demonstrated by Tanduk peel’s ethanol and dichloromethane extracts against S. aureus (30 mm) and C. krusei (10 mm), respectively. However, the least active bacteria and fungi were found to be V. parahaemolyticus and C. albicans, respectively. The minimum inhibitory concentration (MIC) values ranged from 6.25 to 100 mg/mL. Tanduk peel’s ethanol extract exhibited the lowest MIC and minimum bactericidal concentration (MBC) values against B. cepacia (6.25 mg/mL) whereas for fungi, Tanduk peel’s dichloromethane extract exhibited lowest MIC and minimum fungicidal concentration (MFC) values against C. albicans (25 mg/mL). The results of MBC or MFC showed that some extracts were bactericidal or fungicidal while others were bacteriostatic or fungistatic against certain microbes. Banana peel waste’s extracts could be potential antimicrobial alternatives and may be effective to utilize as a natural source of antimicrobial agent in pharmaceutical industries.